Interpreting the concept of sedimentation in Husserl’s Origin of Geometry - Blomberg, Johan (Public Journal of Semiotics, 2020)
In the influential text Origin of Geometry, Edmund Husserl argues that even the invariant meaning found in theoretical disciplines like geometry has a historical becoming: through gradual abstraction and stabilization, ending in a completely rational discipline. This is a process which Husserl proposes is due to language and other symbolic systems. In the absence of a system allowing for stable communication of meaning, geometry or any other tradition would constantly have to begin anew. At the same time Husserl also sees the historical process of meaning stabilization in linguistic form as detrimental. It allows for a reception of an established meaning, which simultaneously entails the forgetfulness of the experiential basis and intuitive knowledge that made ideality possible in the first place. Husserl calls this Janus-faced dialectical process between discovery and forgetfulness sedimentation. This paper analyzes this concept in Origin of Geometry and places it in the context of Husserl’s thought more generally. In contrast to Husserl’s negative view of the effects that sedimentation has for an authentic meaning, I discuss four interpretations of sedimentation that provide more constructive perspectives on the concept. These interpretations also differ considerably from one another, a fact which speaks both to the richness and the tensions in Origin of Geometry.